(untitled) (Castilla. Estudios de Literatura, 2017)
The narrative works of Rafael Courtoisie present a series of stylistic and rhetorical peculiarities that create singular modes of generation of fictional sense far beyond the form. This article analyzes the novel Vida de perro (1997), that is composed of 53 heterogeneous and narratologically disjointed literary fragments. The thesis that will be defended here is that this novel reaches its coherence and unity of meaning through the opposition of all its fragments to what Agamben calls “anthropological machine”, that is, the set of visions and discourses that have historically conceived human being in opposition to animals.